Alternative Happiness in Healing Fiction Welcome to Hyunam-Dong Bookshop - Ayu Triria Puspita Devi; Dewi Suryanti (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study examines the construction of happiness in Welcome to Hyunam-dong Bookshop through Sara Ahmed’s concepts of happy objects and alternative happiness. As part of the growing trend of healing fiction, the novel reflects contemporary experiences of burnout, emotional exhaustion, and dissatisfaction shaped by neoliberal ideals of productivity and achievement. Using a qualitative descriptive method and close reading, this research explores how the characters’ conflicts reveal tensions between socially prescribed expectations and personal desires. The findings show that happiness is initially constructed through socially valued “happy objects,” including marriage, career success, financial stability, family harmony, and educational achievement. These ideals orient individuals toward a normative vision of the “good life.” However, the novel also critiques the limitations of such expectations. This study proposes the concept of alternative happiness, which emerges when characters consciously reorient themselves away from socially prescribed paths. Drawing on Ahmed’s ideas of the feminist killjoy, unhappy queer, and melancholic migrant, the analysis demonstrates that refusal, misalignment, and unresolved emotions can become productive spaces for redefining happiness. Rather than a fixed outcome, happiness is reimagined as a relational process and an ethical choice. This study contributes to literary scholarship by positioning happiness as a critical analytical lens and by expanding the study of healing fiction beyond therapeutic comfort toward critical reflection. It also highlights literature’s pedagogical potential in fostering self-awareness, emotional literacy, and critical engagement with dominant narratives of success and fulfillment.